Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen; Management Group of the EAN Dementia and Cognitive Disorders Scientific Panel (Journal of Alzheimer's disease, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: postakutní syndrom COVID-19; Neuroimmunomodulation; mozek; neurozobrazování; dementia; Humans; komorbidita; lidé; Alzheimer Disease; Biomarkers; Alzheimer’s disease; Alzheimerova nemoc; cognition; Post-Acute COVID-19 Syndrome; péče o pacienta; COVID-19; biologické markery; Comorbidity; Brain; Cognitive Dysfunction; neuroimunomodulace; Patient Care; SARS-CoV-2; kognitivní dysfunkce; Neuroimaging